Keewaywin (journeys) : AIDS in the First Nations - Broman, Doug; AIDS Committee of Thunder Bay; Canada Health and Welfare Canada; AIDS Committee of Toronto Collection - York University (AIDS Committee of Thunder Bay, 1990)
The AIDS Committee of Thunder Bay saw a real need to bring information about this disease to First Nations communities. Research showed that there was scant information about AIDS for First Nations members. The agency applied for and received funding from Health and Welfare Canada to create the video so that information could go directly to isolated areas and communities. "Keewaywin (Journeys), AIDS in the First Nations," speaks about the facts and the myths and is designed to get people interested in discussing the important public health issues surrounding AIDS/HIV infection. AIDS Committee of Thunder Bay produced, directed, written by Doug Broman. Vern Harper, Billy Merasty, Michael Linklater, Teresa Linklater, Shirley Mishibinijima, Eugene Simon, James R. Lawlis, Mary Magiskan. VHS. AIDS Committee of Toronto, Summer, 2010. Donation.